Probing the paradox: are governments fighting or fueling disinformation? - Dragomir, Marius (Frontiers in Communication, 2025)
Over the past decade, disinformation has been the subject of intensive analysis, with researchers examining it from a multitude of perspectives. Among the chief architects of disinformation are governments, which often find themselves playing a double-edged role: both fueling the fire with propaganda and manipulative narratives while simultaneously crafting laws and regulations to combat disinformation. This article seeks to unpack a paradoxical dynamic where governments straddle the line between instigators and regulators of disinformation. Drawing insights from cross-country comparative studies, it delves into the interplay between the independence of public and state-controlled media and key factors like democratic quality, media freedom, and public integrity, in nations that have adopted anti-disinformation legislation. The findings unveil that such laws, which frequently curtail press freedom, are predominantly championed by authoritarian regimes or flawed democracies, wielding them as instruments of censorship. What sets alarm bells ringing, however, is the ripple effect of these practices, which are making inroads into countries known for their strong democratic foundations and well-established traditions of media freedom.